2017
DOI: 10.1111/ecc.12801
|View full text |Cite
|
Sign up to set email alerts
|

On being a caregiver: The experiences of South African family caregivers caring for cancer patients

Abstract: The purpose of our study was to describe the experiences of family caregivers of cancer patients using the public healthcare system in South Africa. We used a qualitative descriptive design and conducted in-depth interviews with 20 purposively selected family caregivers. Data saturation determined the sample size, and qualitative content analysis was used to analyse the data. Three themes arose from the data: emotional responses and feelings towards the cancer diagnosis, fulfilling the role of the caregiver an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(52 citation statements)
references
References 43 publications
4
47
1
Order By: Relevance
“…6 Mostly women take on the caregiving role, usually without prior expertise, and many struggle to balance caregiving responsibilities with their everyday activities, family life, work, and social relationships. 11 Positive consequences of informal caregiving include becoming more focused on priorities in the deeper sense of life and appreciation of life and support from other people. 12 However, psychological distress is common in caregivers, [13][14][15] and often severe caregiver burden spans across physical, psychological, financial, and social domains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Mostly women take on the caregiving role, usually without prior expertise, and many struggle to balance caregiving responsibilities with their everyday activities, family life, work, and social relationships. 11 Positive consequences of informal caregiving include becoming more focused on priorities in the deeper sense of life and appreciation of life and support from other people. 12 However, psychological distress is common in caregivers, [13][14][15] and often severe caregiver burden spans across physical, psychological, financial, and social domains.…”
Section: Introductionmentioning
confidence: 99%
“… 6 Mostly women take on the caregiving role, usually without prior expertise, and many struggle to balance caregiving responsibilities with their everyday activities, family life, work, and social relationships. 11 …”
Section: Introductionmentioning
confidence: 99%
“…(25). Although some participants reported to have more than one source of income, it was perceived as not enough, given the high cost of managing cancer (1). Poverty exacerbated the caregiver burden of families that had no constant source of income, this was confirmed in this study as participants reported extreme difficulty in providing adequate care due to the lack of funds to finance care giving resources (1).…”
Section: Financial Challenges Due To the Cancer Diagnosismentioning
confidence: 61%
“…Cancer is one of the non-communicable diseases (NCDs) that is increasingly becoming part of the leading public health problems, globally (1). It is estimated that 1 in 4 people in South Africa are affected by cancer, annually, either by having a family member or friend diagnosed with cancer or by personally being diagnosed with cancer (1). Cancer diagnosis has a greater impact on family members than on patients.…”
Section: Introductionmentioning
confidence: 99%
“…South Africa faces unique challenges in terms of cancer control due to late presentation, high mortality, healthcare provision, knowledge of cancer (Morhason‐Bello et al, ) and poverty (Maree, Moshima, Ngubeni, & Zondo, ). In addition, the public health system, serving approximately 80% of the population, is under tremendous pressure and experiences expanding demands, lack of personnel and finances, and poor administration (Benatar, ).…”
Section: Introductionmentioning
confidence: 99%